Preparation optimization of ATO particles by robust parameter design. (February 2016) - An, Qi; Bai, Genghua; Yang, Yang; Wang, Cui; Huang, Quehong; Liu, Chao; Chen, Shujun; Cao, Jun; Zheng, Sisi; Gu, Zhengui; Xiang, Bin
Abstract: 3-level-3-factor robust parameter design and variance analysis were employed to optimize the formulatimemon process of antimony doped tin oxide (ATO) particles with high conductivity. Results indicated that optimized formulation parameters were as follow: Sb doped content of 11 mol%, calcination temperature of 800 °C and calcination time of 0.75 h. For the ATO powder prepared under the above optimal condition, the conductivity of ATO in the validation experiment was 7.6511 S cm −1, which was almost close to the predicted value, and the ATO powder had smaller diameter, higher transmittance in visible region as well as better thermal insulating properties than its counterparts.